Orthogonally polarized dual-wavelength Nd:LaMgAl11O19/Nd:SrAl12O19 laser at 1297 and 1306 nm with adjustable ratio of output powers - Chu Chu; Xinghua Yang; Yuzhao Li (PLoS ONE, 2025)
Using tunable in-band laser diode (LD) pumping (791.1–798.2 nm), an orthogonally polarized dual-wavelength (OPDW) Nd:LaMgAl11O19/Nd:SrAl12O19 (Nd:LMA/Nd:SA) operation at 1297 nm and 1306 nm for the 4F3/2 → 4I13/2 transition is demonstrated for the first time. Optimization of LD temperature and pump focus position enabled efficient generation of both wavelengths at balanced power. The maximum combined continuous-wave (CW) output reached 3.32 W at 1297 nm and 1306 nm with a near 1:1 power ratio. Relative to the absorbed 796.56 nm pump power, the laser achieved maximum total slope efficiency and optical-to-optical conversion efficiency of 20.7% and 18.5%, respectively. This 1297 nm and 1306 nm OPDW source shows significant potential for medical and scientific applications.